2018
DOI: 10.7717/peerj.4312
|View full text |Cite
|
Sign up to set email alerts
|

A new Python library to analyse skeleton images confirms malaria parasite remodelling of the red blood cell membrane skeleton

Abstract: We present Skan (Skeleton analysis), a Python library for the analysis of the skeleton structures of objects. It was inspired by the “analyse skeletons” plugin for the Fiji image analysis software, but its extensive Application Programming Interface (API) allows users to examine and manipulate any intermediate data structures produced during the analysis. Further, its use of common Python data structures such as SciPy sparse matrices and pandas data frames opens the results to analysis within the extensive eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…e . 49–64 nm [15, 23, 33] and with a study showing that an average of 5 spectrin proteins converge per junctional complex in the RBC membrane skeleton [34]. Given its unusual amino acid composition and predicted disordered domains [10], we also considered the possibility that KAHRP adopts a highly elongated shape.…”
Section: Discussionmentioning
confidence: 99%
“…e . 49–64 nm [15, 23, 33] and with a study showing that an average of 5 spectrin proteins converge per junctional complex in the RBC membrane skeleton [34]. Given its unusual amino acid composition and predicted disordered domains [10], we also considered the possibility that KAHRP adopts a highly elongated shape.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that hepatocyte actin accumulates around the PVM and important actin reorganization events take place during parasite growth 57 . A recent work demonstrated that this is the case also in erythrocytes infected by P. falciparum 58 . Our results support these reports.…”
Section: Discussionmentioning
confidence: 85%
“…Proteins associated with junctional complexes such as adducin and tropomyosin also are lost from the cytoskeleton, indicating that some remodeling or dismantling occurs. This is accompanied by an increased spectrin mesh size and the temporal appearance of holes in the cytoskeleton (135,136). This might be the gradual process of dissolving the iRBC cytoskeleton described previously (112), but it is unclear why egress would start so early, since the structural integrity must still be maintained until the merozoites are fully developed.…”
Section: Schizont Stagementioning
confidence: 89%